Applications of evolutionary computation EvoApplications 2011: EvoCOMNET, EvoFIN, EvoHOT, EvoMUSART, EvoSTIM, and EvoTRANSLOG, Torino, Italy, April 27-29, 2011, Proceedings, Part II - Chio, Cecilia Di.; Brabazon, Anthony; Caro, Gianni A.; Drechsler, Rolf.; Farooq, Muddassar; Grahl, Jörn.; Greenfield, Gary.; Prins, Christian; Romero, Juan.; Squillero, Giovanni; Tarantino, Ernesto; Tettamanzi, Andrea G. B.; et al. (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the International Conference on the Applications of Evolutionary Computation, EvoApplications 2011, held in Torino, Italy, in April 2011 colocated with the Evo* 2011 events. Thanks to the large number of submissions received, the proceedings for EvoApplications 2011 are divided across two volumes (LNCS 6624 and 6625). The present volume contains contributions for EvoCOMNET, EvoFIN, EvoIHOT, EvoMUSART, EvoSTIM, and EvoTRANSLOC. The 51 revised full papers presented were carefully reviewed and selected from numerous submissions. This volume presents an overview about the latest research in EC. Areas where evolutionary computation techniques have been applied range from telecommunication networks to complex systems, finance and economics, games, image analysis, evolutionary music and art, parameter optimization, scheduling, and logistics. These papers may provide guidelines to help new researchers tackling their own problem using EC.
Electronic reproduction.
Keywords: Computer science; Evolutionary computation -- Congresses; Electronic books